The Use of Artificial Intelligence (AI) In the Management Processes of Communication Between Medical Facility and Patient - Recommendations for Managers of Healthcare Entities - Tomasz DRYL (Communications of International Proceedings, 2023)
This research article discusses the growing challenges in the healthcare sector, focusing on the key role of effective communication between medical facilities and patients. The article highlights the limitations of traditional communication methods in the face of increasing demands and expectations. In response to these challenges, the authors explore the potential of using artificial intelligence (Artificial Intelligence (AI)) in medical communication. They highlight Artificial Intelligence (AI)'s ability to process large amounts of data, analyse patterns and learn, which could revolutionise the way information is communicated and interpreted in the health sector. The article explores in detail how AI technologies can contribute to the personalisation of care, the monitoring of patient health and the effective management of information flows. At the same time, the author highlights the challenges of introducing AI in medical communication, including technical, ethical and legal issues such as the reliability of AI systems, data security, patient privacy and autonomy of medical decisions. The article emphasises the need to understand how patients and healthcare professionals adapt to new technologies and what their expectations of such communication are The aim of the article is to explore the role of AI in medical communication, assess its impact on the quality of healthcare and identify the main challenges and limitations of its implementation. The author used a comprehensive methodological approach, combining analysis of the scientific literature with empirical research, to deepen the understanding of the role of AI in the health sector and to identify directions for further research and development in this rapidly evolving field.
Keywords: management in healthcare; communication in healthcare; AI in medical facilities